Validation of the 24, 25-dihydroxyvitamin D3 to 25-hydroxyvitamin D3 ratio as a biomarker of 25-hydroxyvitamin D3 clearance. Issue 217 (March 2022) - Hsu, Simon; Zelnick, Leila R.; Lin, Yvonne S.; Best, Cora M.; Kestenbaum, Bryan R.; Thummel, Kenneth E.; Hoofnagle, Andrew N.; de Boer, Ian H.
Highlights: The vitamin D metabolite ratio is a strong surrogate measure of 25-dihydroxyvitamin D3 clearance. The vitamin D metabolite ratio is biased by race, kidney disease, and serum albumin. Studies assessing the vitamin D metabolite ratio should adjust for the above covariates. Abstract: The formation of 24, 25-dihydroxyvitamin D (24, 25(OH)2 D) from 25-hydroxyvitamin D (25(OH)D) is the primary mechanism for the metabolic clearance of 25(OH)D, and is regulated by tissue-level vitamin D activity. The ratio of 24, 25(OH)2 D3 to 25(OH)D3 in blood (vitamin D metabolite ratio, VDMR) is postulated to be a marker of 25(OH)D3 clearance, however this has never been tested. We measured baseline 24, 25(OH)2 D3 and 25(OH)D3 concentrations in 87 participants by liquid chromatography-tandem mass spectrometry. Following an infusion of deuterated 25(OH)D3, blood samples for each participant were collected over 56 days and analyzed for deuterated vitamin D metabolites. 25(OH)D3 clearance and the deuterated metabolite-to-parent AUC ratio (ratio of the AUC of deuterated 24, 25(OH)2 D3 to that of deuterated 25(OH)D3 ) were calculated. We compared the VDMR with these two measures using correlation coefficients and linear regression. Participants had a mean age of 64 ± 11years, 41 % were female, 30 % were self-described Black, 28 % had non-dialysis chronic kidney disease (CKD) and 23 % had kidney failure treated with hemodialysis. The VDMR was strongly correlated with 25(OH)D3 clearance and the deuterated metabolite-to-parent AUC ratio (r = 0.51 and 0.76, respectively). Adjusting for 25(OH)D3 clearance or the deuterated metabolite-to-parent AUC ratio in addition to clinical covariates, lower VDMR was observed in participants with CKD and kidney failure than in healthy controls; in Black than White participants; and in those with lower serum albumin. Our findings validate the VDMR as a measure of 25(OH)D3 clearance. This relationship was biased by characteristics including race and kidney disease, which warrant consideration in studies assessing the VDMR.